The Development of Monopoly Physics Science Media (MOFIN) on Simple Harmonic Motion at MA Al-Falah Tolutu - Rahman, Abd; Yunginger, Raghel; Payu, Citron S.; Abdjul, Tirtawaty; Jahja, Mohamad; Setiawan, Dewa Gede Eka (Department of Physics Education, Universitas Mataram, 2023)
This research aims to determine the design and feasibility of the MOFIN learning media. This research model employs the 4D method (Define, Design, Development, and Dissemination). Data collection techniques include interviews (initial stage), observations, and tests (experimental stage). The validity of the MOFIN learning media design obtained an average scale of 3.43 from the validators, with the